Reducing Carbon Footprint in Cooking: A Study on Energy Efficiency and Environmental Impact - Kamdem, Yves Stéphane (International Journal of Scientific Research and Management (IJSRM), 2024)
The study investigates the potential reduction in carbon emissions during cooking by using air-based insulators and automated flame reduction systems. The primary focus is on minimizing heat losses to the environment and boiling inefficiencies. The study includes simulations data to quantify energy savings and equivalent carbon footprint reduction, both at the household and community levels. The findings support the development of a prototype device aimed at improving cooking efficiency. Design requirements, potential risks, failure modes, and practical implications are discussed. The paper provides a comprehensive analysis, supported by simulations, explanatory drawings, and graphs.